Advances in Centrifugal Gravity Concentration – Beyond Low Mass Yield - Ish Grewal (Canadian Institute of Mining, Metallurgy and Petroleum, 2009)
"Batch centrifugal gravity concentrators, which produce very high ratios of concentration, have become common place for recovering free gold within milling circuits. Their effectiveness has proven to be especially useful in recovering finer gold particles. The knowledge related to testing, modeling and scale-up of these systems has been well established over the recent decade mostly due to the efforts of the late Dr. Andre Laplante.Gravity separation technologies such as jigs, spirals and shaking tables can provide the increased mass yields required for minerals that occur at higher concentrations than gold, however their effectiveness tends to diminish at finer particle sizes. The development of high mass yield centrifugal concentrators has provided the opportunity to be able to recover a wide range of minerals at finer particle size classes when compared to the more traditional gravity concentration devices. These concentrators also provide additional benefits such as smaller unit footprint and automated operation.This paper discusses the background, current practices and future applications for high mass yield centrifugal concentrators in base metals, sulfides and industrial minerals. Bench scale, pilot scale and plant practice examples are also presented.INTRODUCTIONGravity concentration, one of the oldest mineral beneficiation processes, has evolved over the decades and continues to play an important role in modern mineral processing operations. The development and growth of froth flotation in the early part of the twentieth century led to a decline in the importance of gravity concentration. However, gravity concentration continued to be used for ores that are difficult to beneficiate using froth flotation; such as tin, tungsten, niobium/tantalum, iron, industrial minerals and oxidized coal. In recent decades, many operations have begun to employ a combination of both gravity concentration and froth flotation Since flotation relies on surface chemistry and gravity concentration relies on specific gravity differences, putting these techniques in series provides today’s metallurgist with unprecedented opportunities to maximize grade and recovery of many of these minerals."